Spanish transfer effects in the english writing of elementary school students - Reppen, Randi; Grabe, William (Lenguas Modernas, 2017)
This paper investigates the language-specific influences in L1 Spanish and L1 English elementary students writing in English. A total of 545 texts (311 English L1; 234 Spanish L1) were analyzed for various linguistic features such as pronoun use, modal verbs, coordination and subordination features. The results from these analyses were then compared with the results of other studies with adult writers. Results appear to confirm a number of earlier assertions about the Spanish L1 transfer effects when writing in English, particularly with regard to the use of elaborate style. This paper also confirms the usefulness of léxico-syntactic analyses as a means for exploring text variation and discourse function from a contranstive rhetoric perspective.